Exposure–response model for sibutramine and placebo: suggestion for application to long-term weight-control drug development - Han S; Jeon S; Hong T; Lee J; Bae SH; Park WS; Park G; Youn S; Jang DY; Kim KS; Yim DS (Dove Medical Press, 2015)
Seunghoon Han,1,2 Sangil Jeon,1,2 Taegon Hong,1,2 Jongtae Lee,1,2 Soo Hyeon Bae,1,2 Wan-su Park,1,2 Gab-jin Park,1,2 Sunil Youn,1,2 Doo Yeon Jang,1,2 Kyung-Soo Kim,3 Dong-Seok Yim1,2 1Department of Pharmacology, College of Medicine, The Catholic University of Korea, 2Pharmacometrics Institute for Practical Education and Training, 3Department of Family Medicine, Seoul St Mary’s Hospital, Seochogu, Seoul, Republic of KoreaAbstract: No wholly successful weight-control drugs have been developed to date, despite the tremendous demand. We present an exposure–response model of sibutramine mesylate that can be applied during clinical development of other weight-control drugs. Additionally, we provide a model-based evaluation of sibutramine efficacy. Data from a double-blind, randomized, placebo-controlled, multicenter study were used (N=120). Subjects in the treatment arm were initially given 8.37 mg sibutramine base daily, and those who lost <2 kg after 4 weeks’ treatment were escalated to 12.55 mg. The duration of treatment was 24 weeks. Drug concentration and body weight were measured predose and at 4 weeks, 8 weeks, and 24 weeks after treatment initiation. Exposure and response to sibutramine, including the placebo effect, were modeled using NONMEM 7.2. An asymptotic model approaching the final body weight was chosen to describe the time course of weight loss. Extent of weight loss was described successfully using a sigmoidal exposure–response relationship of the drug with a constant placebo effect in each individual. The placebo effect was influenced by subjects’ sex and baseline body mass index. Maximal weight loss was predicted to occur around 1 year after treatment initiation. The difference in mean weight loss between the sibutramine (daily 12.55 mg) and placebo groups was predicted to be 4.5% in a simulation of 1 year of treatment, with considerable overlap of prediction intervals. Our exposure–response model, which included the placebo effect, is the first example of a quantitative model that can be used to predict the efficacy of weight-control drugs. Similar approaches can help decision-making during clinical development of novel weight-loss drugs. Keywords: weight-reducing drugs, obesity, pharmacokinetics, pharmacodynamics